Strong Association between Inotrope Administration and Intraventricular Hemorrhage, Gestational Age, and the Use of Fentanyl in Very Low Gestational Age Infants: A Retrospective Study - Theodora Stathopoulou; Eleni Agakidou; Christos Paschaloudis; Angeliki Kontou; Ilias Chatzioannidis; Kosmas Sarafidis (MDPI AG, 2023)
This was a single center, retrospective cohort study designed to evaluate the association between the administration of inotropes to hypotensive very low gestational age infants (VLGAI) and prenatal and neonatal risk factors. Inpatient medical records were reviewed to identify neonates treated with inotropes (treated group) and a control group for comparison. Two hundred and twenty two (222) VLGAI (less than 32 weeks' gestation) were included in the final analysis and were stratified based on timing of treatment with 83 infants (37.4%) and 139 infants (62.6%) in the treated and control groups, respectively. A total of 56/83 (67%) received inotropes for arterial hypotension during the first 3 days (early treatment subgroup) and 27/83 (32.5%) after 3 days of life (late-treated subgroup). Fentanyl, severe intraventricular hemorrhage (IVH), and gestational age (GA) were the risk factors most significantly associated with the need for inotrope use both during the first 3 days of life and the whole NICU stay, before and after adjustment for confounders. In conclusion, fentanyl, severe IVH, and GA are the risk factors most strongly associated with the need for inotrope treatment in VLGAI. Measures to modify these risk factors may decrease the need for cardiovascular medications and improve outcomes.